Faktor-Faktor Pendorong Prestasi Belajar Peserta Didik Di Makassar - Mario Mario (Institut Nalanda, 2024)
Making the nation's life intelligent is one of the ideals of the Indonesian nation as stated in the preamble to the 1945 Constitution. One way to achieve this ideal is through education. The Indonesian government itself has carried out many programs so that all the nation's children can receive a good education. Starting from the 9 year compulsory education program, scholarships for needy students, and many other programs. Education cannot be separated from the learning process. Learning is a process to increase human knowledge and increase one's self-value so that one can survive in everyday life. In the world of education, increasing human knowledge and self-value is often associated with the academic achievements achieved by the student. Measuring academic achievement is very important because it aims to evaluate the development of individual abilities in the educational process. The academic achievements achieved are also a measure of the success of an educational institution in educating its students.